Trajectories of metabolic risk factors and risk of new-onset atrial fibrillation among men and women. (14th October 2021) - Lu, Z; Tilly, M.J; Aribas, E; Roeters Van Lennep, J.E; Ikram, M.A; De Groot, N.M.S; Van Rosmalen, J; Kavousi, M
Abstract: Background: Atrial fibrillation (AF) is the most common cardiac arrhythmia with major public health impact. Obesity and hypertension are among the most important risk factors to AF development. The link between AF and its pathogenetic factors are complex and comprehensive assessment of the impact of various long-term trajectories of anthropometric measures and blood pressure on incident AF among men and women is sparse. Purpose: To investigate sex-specific trajectories of various anthropometric measures and blood pressure at population level, and further assess the impact of these trajectories on incident AF. Methods: We included 5263 participants (mean age 72.1 years) with available repeated assessments measured 2 to 4 times for weight, body mass index (BMI), hip circumference (HC), waist circumference (WC), waist-to-hip ratio (WHR), systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP) and mean arterial pressure (MAP). Latent class linear mixed model with age as the time scale were fitted to identify the potential various classes in each risk factor. Cox proportional hazards regression models were used to assess the association between risk factors' trajectories and risk of new-onset AF, with the most favorable trajectory as a reference. Models were adjusted for traditional cardiovascular risk factors. Results: 2159 (41.0%) of all participants were men. Median follow-up time was 9.76 years during which the incidence rate of AF was 16.2 per 1000 person-years for men, and 11.3 per 1000 person-years for women. In full-adjusted model, various trajectories of BMI, HC, and MAP were significantly associated with incident AF among men, and trajectories of weight, BMI, WC, HC, SBP, PP and MAP were significantly associated with incident AF among women. For BMI, persistent-increasing BMI trajectory carried the highest risk for AF with hazard ratio (HR) and 95% confidence interval (95% CI) of 1.39 (1.05–1.85) in men and 1.60 (1.19–2.15) in women. Also, persistently increasing trajectories of weight [1.69 (1.20–2.37)], WC [1.39 (1.04–1.86)] and HC [1.56 (1.05–2.34)] among women conferred the largest risks. For SBP, the persistently hypertensive trajectory carried the largest risk for AF among women [2.06 (1.25–3.39)], while intensively increasing SBP trajectory conferred the largest risk among men [1.34 (0.89–2.02)], albeit non-significant. Similar associations were observed for MAP among men and women; associated risks were 1.77 (1.25–2.51) for the persistent-hypertensive trajectory in women and 1.64 (1.16–2.33) for the intensive-increasing trajectory in men. Conclusions: Various trajectories of metabolic risk factors were associated with new-onset AF among men and women. Sex-specific associations between SBP and MAP with AF could imply the differential long-term impact of vascular function on AF development among men and women. This highlights the importance of sex-specific preventive strategies for AF in general population. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Gender and Prevention grant, ZonMwCSC scholarship for PhD research